2002
DOI: 10.1093/hmg/11.17.1997
|View full text |Cite
|
Sign up to set email alerts
|

A missense mutation disrupting a dibasic prohormone processing site in pro-opiomelanocortin (POMC) increases susceptibility to early-onset obesity through a novel molecular mechanism

Abstract: The functional loss of both alleles of the human pro-opiomelanocortin (POMC) gene leads to a very rare syndrome of hypoadrenalism, red hair and early-onset obesity. In order to examine whether more subtle genetic variants in POMC might contribute to early-onset obesity, the coding region of the gene was sequenced in 262 Caucasian subjects with a history of severe obesity from childhood. Two children were found to be heterozygous for a missense mutation, R236G, which disrupts the dibasic cleavage site between b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
161
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(168 citation statements)
references
References 31 publications
5
161
0
2
Order By: Relevance
“…In addition, a patient with a compound heterozygous mutation in the PC1 gene that results in nonfunctional PC1 had severe childhood obesity (35). Similar obese conditions were found in a patient with a defect in POMC processing (36). As PC1 and PC2 are essential for the processing of a variety of proneuropeptides, alterations in the expression and protein biosynthesis of PC1 and PC2 are likely to have profound effects on neuropeptide homeostasis.…”
Section: Introductionmentioning
confidence: 81%
“…In addition, a patient with a compound heterozygous mutation in the PC1 gene that results in nonfunctional PC1 had severe childhood obesity (35). Similar obese conditions were found in a patient with a defect in POMC processing (36). As PC1 and PC2 are essential for the processing of a variety of proneuropeptides, alterations in the expression and protein biosynthesis of PC1 and PC2 are likely to have profound effects on neuropeptide homeostasis.…”
Section: Introductionmentioning
confidence: 81%
“…8,9 The majority of these mutations affect either the structure or function of a-and b-melanocyte-secreting hormone (MSH) or the cleavage from their precursor. 9,10,21,22 Two rare mutations in the N-terminal region of the POMC gene, likely affecting processing and sorting of POMC protein to the regulated secretory pathway, have also been associated with early-onset obesity. 11 In the present study, we describe a new mutation in the signal peptide of the POMC gene that inhibits the production and then the overall secretion of POMC protein.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to nonsyndromic obesity, four mutation screening studies involving 601 nonsyndromic obese subjects have shown missense or nonsense mutations in just 7 individuals, implying that coding sequence variation in POMC is a very uncommon cause of nonsyndromic obesity (15)(16)(17)(18). Two genome-screening studies, in French obese sibling pairs and in Mexican-American ex- tended families, suggested strong evidence for linkage of plasma leptin levels to the region of chromosome 2 harboring the POMC gene (19,20).…”
Section: Discussionmentioning
confidence: 99%